Revealing the mechanism of natural product-induced immunogenic cell death: opening a new chapter in tumor immunotherapy - Chen, Yukun; Wang, Zhenzhi; Zhang, Chi; Su, Yisa; Zhou, Tian; Hu, Kaiwen (Frontiers in Immunology, 2024)
This review underscores the role of natural products in inducing immunogenic cell death (ICD) as a key strategy in tumor immunotherapy. It reveals that natural products can activate ICD through multiple pathways-apoptosis, autophagy, pyroptosis, and necroptosis-leading to the release of danger-associated molecular patterns (DAMPs), dendritic cell activation, and improved antigen presentation, which together stimulate a potent anti-tumor immune response.The study also demonstrates the enhanced therapeutic potential of combining natural products with immune checkpoint inhibitors. With a focus on translating preclinical findings into clinical practice, this review consolidates recent discoveries and suggests future research paths, offering both theoretical insights and practical guidance for advancing cancer immunotherapy.